1992
DOI: 10.1111/j.1365-2249.1992.tb02993.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-P30 IgA antibodies as prenatal markers of congenital toxoplasma infection

Abstract: SUMMARYThis study extends a previous study and confirms that the detection of anti-P30 IgA antibodies is very helpful in the diagnosis of acute acquired or congenital toxoplasmosis. Moreover, we demonstrate that an anti-P30 IgA response can be mounted in the fetuses infected by Toxoplasma gondii during their intra-uterine life as early as week 23 of gestation. A double-sandwich ELISA described in our previous work was used to detect anti-P30 IgA antibodies in 1378 human serum samples collected from 551 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(13 citation statements)
references
References 19 publications
1
9
0
3
Order By: Relevance
“…The value of demonstration of IgA T. gondii antibodies in the fetus is now well recognized [642,647,741,743,744]. Therefore, testing for these antibodies for this purpose should be routine in all laboratories that test newborns for suspected congenital T. gondii infection.…”
Section: Immunoglobulin a Antibodiesmentioning
confidence: 97%
“…The value of demonstration of IgA T. gondii antibodies in the fetus is now well recognized [642,647,741,743,744]. Therefore, testing for these antibodies for this purpose should be routine in all laboratories that test newborns for suspected congenital T. gondii infection.…”
Section: Immunoglobulin a Antibodiesmentioning
confidence: 97%
“…Regarding the timing of anti‐ T. gondii antibody production, it is worth mentioning that Decoster et al . suggested that neonatal IgA and IgM could be present only in infections acquired during the third trimester (78). Wallon et al .…”
Section: Compartmentalization Of the Antibody Responsementioning
confidence: 99%
“…IgM and IgA antibodies increase in parallel. Several reports have indicated the role that specific IgA plays in the acute infection process (Decoster et al, 1988;Huskinson et al, 1990;Stepick-Biek et al, 1990;Decoster et al, 1992;Gross et al, 1992;Saathoff and Seitz 1992;Gross et al, 1993). During the course of toxoplasmosis infection, the kinetics of IgA antibodies are similar to those displayed by IgM antibodies (Decoster et al, 1988;Wong and Remington, 1994;; therefore, joint detection of IgA and IgM antibodies may be useful regardless of whether it may be discriminated at the expense of which antibody of reaction proved positive.…”
Section: Discussionmentioning
confidence: 99%